Remembering Reconsidered Ecological And Traditional Approaches To The Study Of Memory - Neisser ,Ulric (Cambridge, Cambridge University Press, 2009)
In Remembering Reconsidered, the new ecologically oriented study of memory makes contact with more traditional approaches. The editors bring together a diverse collection of studies on remembering, using
index